Swine zoonotic viruses: transmission and novel diagnostic technology - Letian Zhang; Zhiwen Jiang; Ying Qin; Yuhai Bi; Shuo Su (One Health Advances)
Abstract Emerging and re-emerging zoonotic viruses pose enormous challenges to public health worldwide. As an important livestock animal, pigs play a vital role in the evolution and spread of many zoonotic viruses. Hence, with the development of globalization and large-scale intensive farming, close human-pig contact increases the threat of zoonotic virus transmission. In this review, to facilitate disease prevention and control efforts, we summarized the prevalence and transmission characteristics of zoonotic viruses associated with pigs, such as influenza virus, coronavirus, and pseudorabies virus. Additionally, we emphasized novel detection techniques including rapid diagnostic tests, biosensor-based detection technology, high-throughput sequencing, and systematic viral epitope scanning. These techniques are instrumental in enabling cost-effective and convenient rapid detection procedures for broader implementation across diverse regions for effective surveillance of viral epidemics. To enhance virus surveillance capabilities and improve strategies for disease prevention in pigs, the improvement of our understanding of viral transmission modes combined with advancements in diagnostic technology is necessary.